1996
DOI: 10.1192/pb.20.12.714
|View full text |Cite
|
Sign up to set email alerts
|

Tardive dyskinesia: screening and risk disclosure

Abstract: A questionnaire was sent to a random sample of 339 psychiatrists on the Royal College mailing list, enquiring about their practice of screening and risk disclosure in patients at risk of tardive dyskinesia. The response rate was 70%. There was wide variation in the rate of informing patients of the risk. Over half of the respondents felt that knowledge about tardive dyskinesia would reduce compliance, a view which predicted a low rate of informing patients. There was support for the issuing of clinical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…However, there is resistance to the informed consent process in many professionals who, despite evidence to the contrary (MacPherson et al . 1996, Chaplin & Kent 1998), feel that information about side‐effects of medication will reduce adherence (Chaplin & Potter 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is resistance to the informed consent process in many professionals who, despite evidence to the contrary (MacPherson et al . 1996, Chaplin & Kent 1998), feel that information about side‐effects of medication will reduce adherence (Chaplin & Potter 1996).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Chaplin & Kent (1998) reported that for stable patients, prescribed maintenance therapy, it was not only safe to provide information regarding tardive dyskinesia, but necessary in order to obtain consent. The view has also been expressed that some psychiatrists are reluctant to provide clients with information as it may result in non‐adherence to treatment (Chaplin & Potter 1996). Furthermore, from a legal point of view it is only required that clients are told a broad view of treatment issues (Stauch 1998, Green 1999).…”
Section: Consentmentioning
confidence: 99%
“…using an Abnormal Involuntary Movements Scale, should take place every 6 months. Clinicians sometimes fear that informing patients about TD may lead to discontinuation; 25 this is clearly insufficient reason not to inform a patient about serious side‐effects. In fact, several studies have found that patients on antipsychotic medications can receive education about TD without this affecting their medication adherence 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatrists increasingly need to have the confidence and ability to discuss potentially negative treatment outcomes with patients. Patients in turn are becoming better informed about their treatment and are more likely to reject the paternalistic approach of many psychiatrists who protect them from such information [14]. A collaborative approach to the therapeutic relationship is therefore encouraged.…”
Section: Discussionmentioning
confidence: 99%